2021
DOI: 10.1002/adfm.202106102
|View full text |Cite
|
Sign up to set email alerts
|

Design of Fire‐Resistant Liquid Electrolyte Formulation for Safe and Long‐Cycled Lithium‐Ion Batteries

Abstract: Turning an unsafe material into a safe one without performance loss for Li-ion battery applications provides opportunities to create a new class of materials. Herein, this strategy is utilized to design a fire-resistant liquid electrolyte formulation consisting of propylene carbonate and 2,2,2-trifluoroethyl groupcontaining linear ester solvents paired with 1 m LiPF 6 salt and fluoroethylene carbonate additive for a Li-ion battery with improved safety and performance. Traditional carbonate-based electrolytes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 31 publications
0
56
0
Order By: Relevance
“…As the main energy storage equipment of electric vehicles, lithium-ion batteries (LIBs) have been widely used for their advantages of low cost, no air pollution problems, and high energy density . However, LIBs have potential safety hazards caused by the flammability of organic carbonate electrolytes . Among them, traditional carbonate solvents with low melting point, such as ethylene carbonate (EC) and dimethyl carbonate (DMC), are not only prone to dehydrogenation when the internal temperature of the battery rises, producing hydrogen or hydroxyl free radicals (H • or • OH) with high reactivity, which further catalyzes the continuous decomposition of electrolytes and increases the potential safety hazard of LIBs in a high-temperature environment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main energy storage equipment of electric vehicles, lithium-ion batteries (LIBs) have been widely used for their advantages of low cost, no air pollution problems, and high energy density . However, LIBs have potential safety hazards caused by the flammability of organic carbonate electrolytes . Among them, traditional carbonate solvents with low melting point, such as ethylene carbonate (EC) and dimethyl carbonate (DMC), are not only prone to dehydrogenation when the internal temperature of the battery rises, producing hydrogen or hydroxyl free radicals (H • or • OH) with high reactivity, which further catalyzes the continuous decomposition of electrolytes and increases the potential safety hazard of LIBs in a high-temperature environment .…”
Section: Introductionmentioning
confidence: 99%
“…2 However, LIBs have potential safety hazards caused by the flammability of organic carbonate electrolytes. 3 Among them, traditional carbonate solvents with low melting point, such as ethylene carbonate (EC) and dimethyl carbonate (DMC), are not only prone to dehydrogenation when the internal temperature of the battery rises, producing hydrogen or hydroxyl free radicals (H • or • OH) with high reactivity, which further catalyzes the continuous decomposition of electrolytes and increases the potential safety hazard of LIBs in a high-temperature environment. 4 Therefore, it is necessary to solve the safety problem of traditional carbonate electrolyte.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The electrolyte formed a rich‐B and rich‐F electrode/electrolyte interface, which dominated the electrochemical feature of the cell. In 2021, An et al 29 demonstrated a fire‐resistant 1 M LiPF 6 in PC‐TFA electrolyte with 2 wt.% FEC for Li(Ni 0.6 Mn 0.2 Co 0.2 )O 2 Li‐ion cells. The chemical structures of PC and TFA are depicted in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Furthermore, it possesses high anodic stability and excellent compatibility with high-nickel cathode. [11] Therefore, rejuvenating PC-containing electrolytes with superior electrochemical compatibility and high performance is significant for developing wide-temperature LIBs.The practical switch from EC to PC in LIBs, nevertheless turns out to be unfortunate, as the formidable co-intercalation and continual decomposition of PC lead to catastrophic exfoliation of graphite and hence failure of batteries. [12,13] Currently, the most common method to tackle this tricky problem is to employ film-forming additives, [14,15] fluorinated solvent [16,17] and novel Li salts [18][19] for forming stable solid electrolyte interface (SEI) on graphite to avoid structural exfoliation.…”
mentioning
confidence: 99%